2012
DOI: 10.1016/j.aquatox.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of diuron and glyphosate in oyster spermatozoa and embryos

Abstract: We investigated the effects of genotoxicant exposure in gametes and embryos to find a possible link between genotoxicity and reproduction/developmental impairment, and explore the impact of chemical genotoxicity on population dynamics. Our study focused on the genotoxic effects of two herbicides on oyster gametes and embryos: glyphosate (both as an active substance and in the Roundup formulation) and diuron. France is Europe's leading consumer of agrochemical substances and as such, contamination of France's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 50 publications
(50 reference statements)
4
76
0
2
Order By: Relevance
“…Also, no morphological changes (FSC: relative size, SSC: relative complexity) were observed upon A. catenella exposure (data not shown). Sperm viability has been widely used in mammalian sperm toxicity tests (Lewis and Ford 2012), but has only been tested in a few aquatic invertebrate species (Favret et al 2010;Akcha et al 2012). In this study, viability of sperm from oysters exposed to A. catenella was not affected.…”
Section: Viabilitymentioning
confidence: 54%
See 1 more Smart Citation
“…Also, no morphological changes (FSC: relative size, SSC: relative complexity) were observed upon A. catenella exposure (data not shown). Sperm viability has been widely used in mammalian sperm toxicity tests (Lewis and Ford 2012), but has only been tested in a few aquatic invertebrate species (Favret et al 2010;Akcha et al 2012). In this study, viability of sperm from oysters exposed to A. catenella was not affected.…”
Section: Viabilitymentioning
confidence: 54%
“…Because bivalves spawn their gametes into the surrounding water, reproductive output could be directly affected by different environmental pollutants (Favret et al 2010;Akcha et al 2012) or HABs (Erard-Le Denn et al 1990; Leverone et al 2006;Basti et al 2011) found there. Cellular parameters of gametes can therefore be used as bio-indicators of modification and disturbance of the environment (Akcha et al 2012). Alterations induced by noxious compounds have been observed in oyster gametes (Nice 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In another study with oyster the relative expression of seven immune-related genes was an equally sensitive endpoint to study the effects of diuron on mollusc (Luna-Acosta et al 2012). Even more sensitive was the study design set up by Akcha et al (2012) where embryo-larval development of oysters were significantly affected by diuron at a concentration of 0.05 µg/l. USEPA has published methods for measuring larval development in oyster (Chapman et.…”
Section: Comparison With Oecd Cf Methodsmentioning
confidence: 99%
“…Diuron has reproductive effects on oyster at a concentration of 0.5 µg/l (Akcha et al 2012). These were genotoxic effects on spermatozoa and not necessary regarded as mediated by endocrine mechanisms.…”
Section: Non-mammalian Toxicologymentioning
confidence: 99%
“…In vivo, oysters exposed to toxic algae revealed alteration of spermatozoa quality (21,25). Gametes of C. gigas are released into the surrounding seawater where they are exposed to various environmental stressors (26,27) and possibly toxic algae (10,(28)(29)(30). Blooms of A. minutum occur during summer, which is concomitant with the oyster spawning period.…”
mentioning
confidence: 99%